PENGARUH CORPORATE SOCIAL RESPONBILITY (CSR), STRUKTUR MODAL, PROFITABILITAS, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAANTERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Nurul Hidayanti, 14.05.52.0149; Nurhayati, Ida (Students Journal of Accounting and Banking, 2018)
This Study aimed to analyze the Corporate Social Responbility (CSR), capital structure, profitability, divident policy,and company size, to ward the firm value. The population in this study are all companies listed on the Indonesia Stock Exchange in 2014 until 2016. The sample of this study was taken by using purposive sampling technique, so that these were 187 companies got for this study. Data analysis tools used in this research is descriptive analysis and multiple regression analysis. The result of this study showed that the Corporate Social Responbility (CSR) has negative and not significant effect on firm value. Capital structure has negative and not significant effect on firm value. Profitability has positive and significant effect on firm value.Â Divident policy has positive and not significant effect on firm value. And company size has positive and significant effect on firm value. Keywords :Company Size, Profitability, Divident Policy, Debt Policy, Firm Value.